Circular RNA Pleiotrophin promotes carcinogenesis in glioma via regulation of microRNA-122/SRY-box transcription factor 6 axis. Issue 2 (March 2020) - Chen, Chen; Deng, Lu; Nie, De-Kang; Jia, Feng; Fu, Lin-Shan; Wan, Zheng-Qiang; Lan, Qing
Abstract : Background: Circular RNAs (circRNAs) are recently identified as gene regulators in mammals and play important roles in carcinogenesis of cancer. For example, circRNA_PTN has been recognized as a biomarker of human cancer and is overexpressed in glioma. The molecular function of circRNA_PTN and its downstream targets in glioma, however, remains elusive. Methods: Quantitative polymerase chain reaction analysis was used to measure the expression of circular RNA pleiotrophin (circ_PTN) and miR-122. 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide, propidium iodide and Annexin-V/propidium iodide assay were performed to determine cell proliferation and apoptosis of glioma cells. Circular RNA Interactome and TargetScan were used to predict the potential microRNA targeting of circ_PTN and the potential targets of miR-122, respectively. Luciferase activity assay was used to validate these interactions. Downstream molecular mechanisms, including SRY-box transcription factor 6 (SOX6), extracellular regulated protein kinases (ERK), Cyclin D1, B-cell lymphoma-2 (BCL-2) and BCL2 associated X, apoptosis regulator (BAX), were determined by western blot. Results: Circ_PTN was overexpressed in glioma cells, and its knockdown induced cell proliferation inhibition, cell cycle arrest and apoptosis in glioma cells. The target microRNA of circ_PTN was predicted to be miR-122, the expression of which was negatively correlated with circ_PTN in glioma cells. Moreover, SOX6 was predicted as a potential target of miR-122, and miR-122 overexpression decreased SOX6 expression. MiR-122 inhibitor reversed the tumor-suppressing effects of circ_PTN knockdown, while overexpression of SOX6 impaired the miR-122 overexpression-induced cell growth inhibition and apoptosis. In addition, mitogen activated kinase-like protein (MAPK)/ERK pathway was involved in circ_PTN/miR-122/SOX6 axis. Conclusions: Circ_PTN acted as a sponge of miR-122 and upregulated miR-122 target SOX6, thus promoting carcinogenesis of glioma cells.